Integrating multicriteria decision-making analysis for a GIS-based settlement area in the district of Atakum, Samsun, Turkey - Kilicoglu, Cem; Cetin, Mehmet; Aricak, Burak; Sevik, Hakan (Springer Science and Business Media LLC, 2020)
The last century witnessed a boom in the world population, reaching an unprecedented level. In particular, in recent decades, the population has concentrated in cities. Migration from rural areas to urban areas brings many problems to urban areas, necessitating the opening of new settlement areas. These new settlement areas that are needed are mostly determined in line with the initiatives of local authorities based on the situation of infrastructure facilities, not scientific evaluations. If the wrong places are selected, various natural events each year may cause the loss of property and lives, in addition to significant amounts of energy consumption. This study uses various parameters and creates a method for place selection based on multiple criteria. The district of Atakum in the city of Samsun, which has been subject to continuous migration and where new settlement areas have been established, is selected as the study area. Within the scope of this study, in addition to landslide and flood risks, which constitute the most important natural disasters in the region, situations of high voltage electricity transmission lines in places where the establishment of a residential area would be objectionable are evaluated. The situation of biocomfort, which is significantly important, especially with respect to energy efficiency as well as human health, peace, and comfort, is also evaluated. This study is conducted based on these criteria, and as a result, it calculates that only 15.11% of the district of Atakum is appropriate for use as a settlement area. In addition to serving as a reference for the short- and long-term area planning studies that will be conducted in the region, this study also holds significance due to the new perspective it offers regarding urban planning studies.
Keywords: 13. Climate action; 11. Sustainability; 1. No poverty; 15. Life on land; 7. Clean energy; 12. Responsible consumption; 3. Good health